2011
DOI: 10.1016/j.devcel.2011.07.011
|View full text |Cite
|
Sign up to set email alerts
|

Polo Kinases Establish Links between Meiotic Chromosomes and Cytoskeletal Forces Essential for Homolog Pairing

Abstract: During meiosis, chromosomes must find and align with their homologous partners. SUN and KASH-domain protein pairs play a conserved role by establishing transient linkages between chromosome ends and cytoskeletal forces across the intact nuclear envelope (NE). In C. elegans, a pairing center (PC) on each chromosome mediates homolog pairing and linkage to the microtubule network. We report that the polo kinases PLK-1 and PLK-2 are targeted to the PC by ZIM/HIM-8-pairing proteins. Loss of plk-2 inhibits chromosom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

12
207
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 109 publications
(219 citation statements)
references
References 44 publications
12
207
0
Order By: Relevance
“…Consistent with this arrangement, it has been recently reported that in mouse meiosis KASH5 associates with SUN1 and SUN2, and with cytoplasmic dynein (Horn et al, 2013;Link et al, 2014;Morimoto et al, 2012). Interestingly, it has also been recently demonstrated that different serine/threonine protein kinases phosphorylate the nucleoplasmic domain of SUN1 at the meiotic nuclear envelope in the nematode Caenorhabditis elegans, and that these modifications are required for telomere movement and attachment to the centrosome (Labella et al, 2011;Penkner et al, 2009;Sato et al, 2009).…”
Section: Introductionsupporting
confidence: 48%
See 2 more Smart Citations
“…Consistent with this arrangement, it has been recently reported that in mouse meiosis KASH5 associates with SUN1 and SUN2, and with cytoplasmic dynein (Horn et al, 2013;Link et al, 2014;Morimoto et al, 2012). Interestingly, it has also been recently demonstrated that different serine/threonine protein kinases phosphorylate the nucleoplasmic domain of SUN1 at the meiotic nuclear envelope in the nematode Caenorhabditis elegans, and that these modifications are required for telomere movement and attachment to the centrosome (Labella et al, 2011;Penkner et al, 2009;Sato et al, 2009).…”
Section: Introductionsupporting
confidence: 48%
“…Thus, the cytological and biochemical data together indicate that the phosphorylation of the nucleoplasmic domain of SUN1 by CDK2 could be an important step in regulating SUN1 distribution along the nuclear envelope in spermatocytes. Interestingly, two recent studies have reported that the kinases CHK-2 and PLK-2, by phosphorylating the nucleoplasmic domain of SUN-1 during C. elegans meiosis, do not regulate telomere attachment, but the telomere movement along the nuclear envelope and homolog pairing (Labella et al, 2011;Penkner et al, 2009;Sato et al, 2009). Similarly, in mouse meiosis CDK2 could be responsible for phosphorylating SUN1 to direct the lateral diffusion of these LINC complexes and then move telomeres along the nuclear envelope.…”
Section: /2mentioning
confidence: 99%
See 1 more Smart Citation
“…In C. elegans, the central element includes the factors SYP-1, SYP-2, SYP-3, and SYP-4 (MacQueen et al 2002;Colaiacovo et al 2003;Smolikov et al 2007Smolikov et al , 2009. Loss of any one of these proteins produces a similar mutant phenotype: extensive asynapsis of all chromosomes that is accompanied by a delay in meiotic progression in which chromosomes remain asymmetrically localized in meiotic nuclei (MacQueen et al 2002;Colaiacovo et al 2003;Smolikov et al 2007Smolikov et al , 2009 and factors that normally localize transiently to meiotic chromosomes persist (Harper et al 2011;Labella et al 2011;Rosu et al 2013;Stamper et al 2013;Woglar et al 2013). We have shown that syp-1 mutants also induce germline apoptosis as a result of the synapsis checkpoint ( Figure 1A) (Bhalla and Dernburg 2005).…”
mentioning
confidence: 99%
“…The synapsis checkpoint requires pairing centers (PCs) (Bhalla and Dernburg 2005), cis-acting sites near one end of each chromosome. PCs also promote pairing and synapsis (MacQueen et al 2005) by recruiting factors, such as the zinc-fingercontaining proteins ZIM-1, ZIM-2, ZIM-3, and HIM-8 Phillips and Dernburg 2006), and the conserved polo-like kinase PLK-2 (Harper et al 2011;Labella et al 2011). We have hypothesized that the synapsis checkpoint monitors the stability of pairing at PCs as a proxy for proper synapsis (Deshong et al 2014;Bohr et al 2015).…”
mentioning
confidence: 99%